Investigation of genotoxicity caused by oral isotretinoin use in acne treatment - Derici Eker, Ebru; Kocoglu, Serkar; Ozlen Sahin, Nefise (Annals of Medical Research, 2021)
Aim: Acne vulgaris is an inflammatory disease with a multifactorial origin in the pilosebaceous unit affecting approximately 85% of the population aged 11-23 years. Although it does not present a life-threatening condition, it can cause social phobia and depression due to its psychological and physical effects. Isotretinoin is one of vitamin A-derived retinoids and has been used in moderate and severe acne cases for more than 25 years. Genotoxicity is an expression covering the damage caused by genotoxic substances in DNA structure and chromosomes. Material and Methods: The aim of this study was to investigate whether isotretinoin used orally in the treatment of acne vulgaris has an effect on micronucleus frequency which is one of the most important biomarkers of genotoxicity. The experimantal group consisted of 30 women aged 20-23 years who were diagnosed with acne and used isotretinoin for at least 3 months, and the control group consisted of individuals who did not use isoretinoin with similar properties. Buccal smear samples were taken from all groups and micronucleus test was performed. Results: In the experimental group, the micronucleus frequency was 109.4±13.84. In the control group, the micronucleus frequency was 96.2±10.13. The difference between the experimental and control groups in terms of micronucleus frequency was found to be statistically significant (p=0.026). Conclusions: As a result, it is emphasized that isotretinoin indication should be done more carefully in the treatment of acne and it is very important for the patient, relatives and public health.Keywords: Acne; isotretinoin; genotoxicity; micronucleus test.
Keywords: Acne; isotretinoin; genotoxicity; micronucleus test.